Affirmative action: a comparative perspective - Gerber, Roland (Department of Commercial Law, 2023)
The issue of affirmative action is topical world wide, but is of particular relevance to South Africa, which is attempting to end discriminatory employment practices, and to promote employment opportunities for previously disadvantaged groups. The experience of other countries in striving for employment equity is thus of express interest. This study will, of necessity, be restricted to specific areas. It begins by examining several definitions of affirmative action. This is followed by a discussion of the philosophical rationales for and against affirmative action. The examination then centres on selected international experiences of affirmative action. It then turns to the··· implementation of affirmative action in the South African context, from a constitutional·--. and legislative view, looking at the Green Paper on Employment and Occupational Equity, and highlighting the similarities of Canadian employment equity legislation. The practical implementation of affirmative action in South African companies and local government is then explored. Finally, this study concludes with a discussion of the merit principle, as a guiding policy in the implementation of affirmative action, and a critique of the quota and job reservation system.